Історія виникнення та розвиток старовинних церковних розспівів від Київської Русі до xv століття - Стець, Лілія Леонідівна; Stets, Liliia L. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкриваються витоки, історія розвитку та особливості вітчизняної церковної співочої культури у контексті історіографічних досліджень. В цілому піднято проблему спадковості у вітчизняній музичній культурі, актуалізовані специфічні властивості етнорелігійного світогляду українського народу. The article describes the sources and origin of ecclesiastical chanting in the ancient Kievan Rus and shows its transformation in the process of its historical development. It traces the genesis, establishment, ways of development, and factors of adaptation and canonizing of ancient chants in the historical projection. It also shows the importance, place and functional and meaningful role of chanting. The chronological boundaries of the material under research encompass the 10th – beginning of the 15th centuries. The methodological basis for the research is the teaching of Orthodox Church about divine service, the role and place of chanting in it, resolutions of Ecumenical Councils, chronicles and legacy of ecclesiastics: works of Church teachers, dogmatists, historians, polemists, fathers of the Church of Rus, liturgical and ecclesiastical literature which highlights the main principles of the approach to understanding the charismatic, gnoseological and didactic essence of the church art, and chanting in particular. Since the times of Kievan Rus, ecclesiastical chanting has been the main form of professional music. The adoption of Christianity by Prince Vladimir and the baptizing of Rus in the 10th century initiated Byzantine cultural orientation and the establishment of Byzantine system of values, as it was exactly in the Byzantine Empire where the Orthodox Christian cult was borrowed, together with the culture of choral singing. In Byzantine religious service, music played an important role: it endowed Christian cult with greatness, emphasized its impact on the inner aspect of human soul. Ecclesiastics Basil the Great, John Chrysostom, St. Gregory the Theologian focused on the benefits of church singing for the spiritual development of man, considered it a means of elevation of the soul and its merging with the divine world. Musical culture of Kievan Rus was profoundly influenced by the Byzantine Empire, touching upon all its major aspects. It defined the esthetic direction of Rus’ ecclesiastical music, impacted on its genres, hymnography and the area of usage; it formed the system of notation and recording of ancient Rus’ music. From the first days of introducing Christianity in Rus, Kievan princes invited Greek singers, teachers of ecclesiastical chanting – choristers with their notation, that is mnemonic signs which the Greeks used to write down their eight-chant melodies, spread books which taught singing, and established schools of singing. Almost immediately, ecclesiastical chanting became the business of specially trained people – professionals. This is proved by chronicles which feature names of famous Kievan choristers, as well as resolutions of church Councils. Samples of Byzantine music were creatively adopted by Rus’ masters who modified and improved the original chants. Singing cycles of the times of Kievan Rus are connected with the names of outstanding people, educators of Rus – Princess Olga, Prince Vladimir, called Equal to the Apostles, since they encouraged and spread Christianity in Rus, like apostles. The first sample of Rus’ ecclesiastical chants is considered the mass created to commemorate saint martyrs – princes Boris and Gleb, glorified by the people as patrons and defenders of Rus. Therefore, Byzantine chanting system with its multitude of forms was not adopted mechanically but in a creative way, and it gradually turned into a new original East-Slavonic ecclesiastical-musical language. Byzantine esthetics formed music culture of Kievan Rus, determining the development tendencies in ecclesiastical music long in advance. Church singing which Rus’ ambassadors heard in Constantinople impressed them with its unheard of beauty. The grandeur of Greek mass became one of the main criteria of the truthfulness. The admiration of beauty described in the text of the chronicle shows esthetic readiness, inclination to accept this beauty, which was not simple but very subtle. It was the esthetic aspect which laid the foundation for both Byzantine and ancient Kievan Rus’ musical art because it connected divine service itself with music.
History and deyelopment ofancient eccleciastical chant Kieyan Rus to the XV century
Keywords: духовна музика; церковний розспів; система восьмигласся; демественний спів; sacred music; church chant; the system vosmyhlassya; demestvenn singing